P179 Patient safety alert: a prospective study on 100 patients highlighting inaccuracy of pulse oximeter finger probes used on ear lobes. (December 2018) - Malhotra, P; Shaw, L; Barnett, J; Hayter, E; Hill, N; Stockton, P
Abstract : Introduction: Clinicians often obtain peripheral saturation (SpO2) readings by placing a finger probe sensor on the patient's earlobe when a reading cannot be obtained from the finger. The accuracy of this method is unknown, and is not recommended by the manufacturers of oximeters. Objectives: To assess the accuracy of oxygen saturations measured by a pulse oximeter finger probe on earlobes compared to saturations on arterial blood gases (ABGs). Method: We performed a prospective study on 100 patients attending the oxygen clinic at a teaching hospital from September 2017 to May 2018. All patients who were routinely due to have ABGs performed were included, and informed verbal consent was taken. Saturations were recorded using a Masimo Rad5v oximeter for finger probe on the finger, finger probe on earlobe, and ear probe on earlobe. These were compared to saturations recorded on ABGs performed on the same clinic visit as a gold standard utilising a Radiometer ABL 90 flex ABG machine. We defined 'accurate' SpO2 as being ±2% of the SaO2 on the ABG. The degree of variation of SpO2 from SaO2 was stratified into ≤2%, ≤3%, ≤4%, and >4%. Results: As demonstrated in table 1, using a finger probe on the finger gave the most accurate SpO2 readings compared to the ABG. Using a finger probe on the earlobe was the least accurate with only 7% readings being within ±2% of SaO2. Using a more 'lenient' definition of accuracy as variation of ≤4% compared to SaO2, the accuracy of finger probe on finger, ear probe on earlobe, and finger probe on earlobe were 94%, 79% and 37% respectively. In all cases (n=100), using a finger probe on the earlobe over-estimated the oxygen saturations with values ranging from 0.1% to 12% (mean 5%) greater than SaO2, highlighting that this method was inaccurate, and potentially exposed patients to the risk of clinicians under-estimating the degree of hypoxemia. Conclusions: This study highlights that the practice of using pulse oximeter finger probes on ear lobes when saturations are difficult to record on a finger is inaccurate and potentially risky.